Palm Springs Villager, November 1952, page 20 (1952)
Pictured (L to R): 'Harpo Marx (third from left) broke ground in October for Tamarisk's $250,000 club building. Others are Monte Herbert, Lou Halper, Harry Tugend, M.O. Anderson, William Cody and Paul Addessi.' - Frank S. Partridge, Jr. 'Mr. and Mrs. James E. French and their Pekingese. Mr. French is president of O'Donnell Golf course.' 'Ben Shearer, vice-pres., O'Donnell Golf course, and vigorous supporter of gold in the desert area.' '(1) USGA officials have been invited to visit the winter golf capital this season. In the picture: Joe Dey, exec. sec.,; Charlie Lindeman, pres. Seattle Gold Club; Totten P. Heffelfinger, pres.; John Ames, sec. (2) O'Donnell Gold Club directors: Fred Ingram, Reuben Fleet, J.E. French, pres.,; J.H. Ballinger and Milton Hicks (3) Thunderbird's polo team: Frank Bogart, capt.; Guy Campbell and Harry Merrill. (4) Mrs. M.O. (Vi) Anderson, daughter Mrs. Hugh Becket, and grandchildren. (5) Rip Arnold, Cherry Hills pro; Ben Hogan, A.A. Littler and Monte Moncreit at Thunderbird. (6) Thunderbird's officers and directors: Jack Allgaier, Joe Froggatt, treas.; John Dawson, pres.; Paul Prom, Barney Hinkle (seated) Lou Manseau, vice-pres.; Milt Hicks, Joe Getz, sec.'